2014
DOI: 10.12973/jesr.2014.42.2
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of school administrators about psychological counseling and guidance services: A descriptive study

Abstract: Çalışmanın amacı, okul yöneticilerinin, okullarındaki Psikolojik Danışma ve Rehberlik (PDR) hizmetlerine ilişkin görüşlerini cinsiyet, branş, hizmet yılı, okul türü, okulun bulunduğu yerleşim birimi, okuldaki psikolojik danışman sayısı ve öğrenci sayısı değişkenlerine göre incelemektir. Betimsel yöntemin kullanıldığı alan taraması niteliğindeki araştırmanın grubu, 203 okul yöneticisinden oluşmaktadır. Araştırmanın verileri, araştırmacılarca geliştirilen ve 20 maddeden oluşan ölçme aracı ile elde edilmiştir. Ay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…A study by Friedman, Tidd, Currall, and Tsai (2000) found that the dominating and avoiding conflict management strategies actually increase relational conflict and occupational stress. In another study, Gündüz, Tunç, and İnandı (2013) found that the anger trait positively correlates with the dominating conflict management strategy, while it is negatively correlated with the integrated conflict management strategy. The obliging strategy, however, could pose other problems regarding the effectiveness of communication as it may lead to a perception of weakness for the individual and encourage the counterparty to adopt an imposing approach (Folger et al, 2013).…”
Section: Discussionmentioning
confidence: 92%
“…A study by Friedman, Tidd, Currall, and Tsai (2000) found that the dominating and avoiding conflict management strategies actually increase relational conflict and occupational stress. In another study, Gündüz, Tunç, and İnandı (2013) found that the anger trait positively correlates with the dominating conflict management strategy, while it is negatively correlated with the integrated conflict management strategy. The obliging strategy, however, could pose other problems regarding the effectiveness of communication as it may lead to a perception of weakness for the individual and encourage the counterparty to adopt an imposing approach (Folger et al, 2013).…”
Section: Discussionmentioning
confidence: 92%
“…Studies on the needs assessments of students show that there is a positive relationship between the quality of the guidance services provided and the degree of recognition of the students' guidance needs (Astramovich, 2011). Some studies conducted in this direction show that the guidance needs of students in secondary education are not met at a sufficient level (Apaydın & Çakır, 2016; Güven, 2009;Hatunoğlu & Hatunoğlu, 2006;Nazlı, 2007;Tuzgöl Dost & Keklik, 2012;Yeşilyaprak, 2009;Yüksel Şahin, 2008). It is important to determine whether the guidance needs of the students differ according to some variables and to organize the guidance programs in a way that covers the differing needs of the students (Drefs, 2003;Gordon, 2000).…”
Section: Introductionmentioning
confidence: 99%